Disability studies applied to disability ministry - McNair, Jeff (Review and expositor, 2016)
Ministry that includes persons with developmental disabilities should grow out of an understanding of disability. The models most often used to understand disability are the medical model and the social model. Each is described briefly. We then take these models and unpack how they would lead to the development of ministry. As in human services, we too often develop ministries that are exclusively based on the medical model. However, what would a ministry that grew out of a combination of these models look like? The focus of ministry would be on both developing the individual and changing the environment. This article looks at strategies for facilitating this type of “mature” ministry.